"Assessing the Trends and Impact of Minimum Support Price (MSP) on Agricultural Production: A Study of Wheat, Rice, and Pulses in India" (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2024)
The study titled "Assessing the Trends and Impact of Minimum Support Price (MSP) on Agricultural Production: A Study of Wheat, Rice, and Pulses in India" analyzes the long-term trends in MSP and their correlation with the production of key staple crops from 1991 to 2020. The research identifies a steady increase in MSP for wheat and rice, while pulses exhibit greater volatility, with significant spikes in response to government interventions aimed at reducing import dependence. The production data for wheat and rice show a consistent upward trend closely aligned with MSP increases, indicating strong responsiveness to these price supports. Pulses production, though more variable, also demonstrates growth driven by aggressive MSP policies.The regression analysis confirms a statistically significant relationship between MSP and production for all three crops, with wheat and rice showing the highest sensitivity. The study finds that over 90% of the variations in wheat and rice production can be explained by changes in MSP. Pulses, despite being influenced by external market and climate factors, also exhibit a significant correlation with MSP, though to a lesser extent. The research underscores the effectiveness of MSP as a policy tool in boosting agricultural output, particularly for wheat and rice, while suggesting the need for complementary policies for pulses to enhance production stability. These findings offer critical insights for policymakers on using MSP to ensure food security and agricultural sustainability in India.